Developments on CO2-utilization technologies. Issue 2 (8th May 2019) - Zhu, Qian
Abstract: As an additional CO2 -mitigation strategy to carbon capture and storage, CO2 capture and utilization (CCU) is attracting increasing interest globally. The potential applications of CCU are diverse, ranging from using CO2 in greenhouses and farming to conversion of CO2 into fuels, chemicals, polymers and building materials. CO2 has already been used for decades with mature technologies in various industrial processes such as CO2 -enhanced oil recovery, the food and beverage industry, urea production, water treatment and the production of fire retardants and coolants. There are also many new CO2 -utilization technologies at various stages of development and commercialization. These technologies have the potential to provide opportunities for emission savings for power and other industrial sectors by partially substituting fossil-fuel raw materials, increasing efficiency and using renewable energy, and generating revenues through producing marketable products. This paper investigates the CO2 -utilization technologies that convert CO2 into commercial products via chemical and biochemical reactions with a focus on front-running technologies that are at, or close to, large-scale demonstration or commercialization. The CO2 -utilization technologies are grouped according to the technological routes used, such as electrochemical, photocatalytic and photosynthetic, catalytic, biological process (using microbes and enzymes), copolymerization and mineralization. Recent developments and the status of the CO2 -utilization technologies are reviewed. The environmental impact of CCU is also discussed in terms of life-cycle analysis.